Anisotropies of ultrahigh energy cosmic ray nuclei diffusing from extragalactic sources - Harari, Diego Dario (2015)
We obtain the dipolar anisotropies in the arrival directions of ultrahigh energy cosmic ray nuclei diffusing from nearby extragalactic sources. We consider mixed-composition scenarios in which different cosmic ray nuclei are accelerated up to the same maximum rigidity, so that E